Morphological and ultrastructural study of the efferent ductules in the Chinese soft‐shelled turtle Pelodiscus sinensis. Issue 2 (24th December 2015) - Waqas, Muhammad Yasir; Liu, Tengfei; Yang, Ping; Ahmed, Nisar; Zhang, Qian; Hu, Lisi; Hong, Chen; Chen, Qiusheng
ABSTRACT: Comparative study of the turtle excurrent duct system increases our understanding the evolution of sperm motility and fertility maintenance in higher vertebrates. Therefore, in this study we observed the histology and ultrastructure organization of efferent ductules in the Pelodiscus sinensis using light and transmission electron microscopy. The efferent ductules are extra‐ testicular and 22–28 in number originate from rete testis. The epithelium is entirely composed of two types of cells, the predominant non‐ciliated and ciliated cells. The ciliated cells have long cilia that protrude into the lumen to form a meshwork. These cells associated with clusters of mitochondria in the supranuclear cytoplasm and possess coated vesicles, vacuole, intracellular spaces, and junction complexes. Ciliated cells in the proximal portion of the ductules contain an endocytic apparatus with coated pits and tubules in the apical cytoplasm. Interdigitations and lipid droplets are predominantly present around the nuclei of these cells. The non‐ciliated cells have clusters of mitochondria present in both the supranuclear and perinuclear cytoplasm whereas, the nuclei of these cells are lightly stained. Moreover, the contour of the epithelium towards lumen is irregular as it has a deep indentation. The apical cytoplasm goes deep into the lumen to form cytoplasmic processes. This is the first study to describe the detailed features of efferent ductules in Pelodiscus sinensis with, special focus on the morphology of ciliated cells, as these cells are involved in the mixing of luminal fluid and transport of spermatozoa towards the distal region. J. Exp. Zool. 9999A:XX–XX, 2015. © 2015 Wiley Periodicals, Inc.